NIDRA VS LIFESTYLE DISORDER- AN EAGLE EYE VIEW (International Journal of Ayurveda and Pharma Research, 2020)
Ayurved, the ancient science of life emphasizes on physical and mental health with preventive aspect. “Swasthasya swasthya rakshanam” is the main objective of Ayurved. Curing a diseased person and reshaping his health status is also an aim of Ayurved. The concept of prevention was explained for the very first time in Ayurved and it is now a very basic health aspect of society. Ayurved suggests a balance in the functioning of Dosh, Dhatu and Mala as well as Agni and Ojas along with pleasant status of Atma, Indriya and Manas are the basic requirements to be called as Swasth. To stay healthy one must understand the routine changes occurring in body according to the biological clock as well as seasonal changes. Ayurved advocates to understand the importance of following proper lifestyle as described. Dincharya, Ratricharya and Ritucharya are key important factors to adjust the routine environmental changes. The lifestyle changes in the recent times have led to a huge number of disorders like hypertension, obesity, Diabetes Mellitus, polycystic ovary disease (PCOD), depression, metabolic syndromes, cirrhosis and other diseases of liver and lack of proper sleep or Nidra plays an important role in all of them. Acharyas have explained Nidra, its importance, its relation with Prakriti, Vikriti, its relation with different Ritus methods of proper sleep, consequences of improper Nidra and its management in detail. Here we explain the ancient wisdom of Ayurveda about the importance of ideal Nidra or sleep, Nidranash and role of proper Nidra in various lifestyle disorders.